Wake up and smell the coffee: caffeine supplementation and exercise performance—an umbrella review of 21 published meta-analyses. Issue 11 (29th March 2019) - Grgic, Jozo; Grgic, Ivana; Pickering, Craig; Schoenfeld, Brad J; Bishop, David J; Pedisic, Zeljko
Abstract : Objective: To systematically review, summarise and appraise findings of published meta-analyses that examined the effects of caffeine on exercise performance. Design: Umbrella review. Data sources: Twelve databases. Eligibility criteria for selecting studies: Meta-analyses that examined the effects of caffeine ingestion on exercise performance. Results: Eleven reviews (with a total of 21 meta-analyses) were included, all being of moderate or high methodological quality (assessed using the Assessing the Methodological Quality of Systematic Reviews 2 checklist). In the meta-analyses, caffeine was ergogenic for aerobic endurance, muscle strength, muscle endurance, power, jumping performance and exercise speed. However, not all analyses provided a definite direction for the effect of caffeine when considering the 95% prediction interval. Using the Grading of Recommendations Assessment, Development and Evaluation criteria the quality of evidence was generally categorised as moderate (with some low to very low quality of evidence). Most individual studies included in the published meta-analyses were conducted among young men. Summary/conclusion: Synthesis of the currently available meta-analyses suggest that caffeine ingestion improves exercise performance in a broad range of exercise tasks. Ergogenic effects of caffeine on muscle endurance, muscle strength, anaerobic power and aerobic endurance were substantiated by moderate quality of evidence coming from moderate-to-high quality systematic reviews. For other outcomes, we found moderate quality reviews that presented evidence of very low or low quality. It seems that the magnitude of the effect of caffeine is generally greater for aerobic as compared with anaerobic exercise. More primary studies should be conducted among women, middle-aged and older adults to improve the generalisability of these findings.